Physicochemical, Fatty Acid and Sensory Profile of Cocoa Butter Produced from Fermented and Non-Fermented Cocoa Butter - Novia Andriani; Rina Yenrina; Novizar Nazir (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2020)
The study aimed to explore the influence of fermentation and non-fermentation on cocoa processing (Theobroma cacao L.) on physical properties, chemical properties, fatty acid profiles and sensory properties of cococa butter. The study was conducted using an experimental method with two treatments and three replications. Analysis of cocoa butter consisted of yield, color, moisture content, free fatty acids, iod numbers, peroxide numbers, determination of fatty acid profile using GC-MS, and analysis of sensory properties. The results showed that the yield was between 20.82-21.00%. The color of fermented cocoa butter has a value of L* 17.88, a*8.70, and b*7.99 while for nonfermented cocoa butter has a value of L* 14.88, a* 8.96, and b* 6.78, water content between 0.10-0.12%, free fatty acids 0.51-0.56%, iod numbers 26.40-26.50 g I2/100g, peroxide numbers between 0.40-0.70 meq peroxide/kg fat, 190.23-191.40 mg KOH/g fat. The fatty acid profile using GC-MS showed that the dominant fatty acid constituents contained in fermented and nonfermented cocoa fats are oleic acid (29.39-29.57%), heptadecanoic acid (25.85-26.77%), and palmitic acid (21.49-21.83%). Based on sensory analysis of cocoa butter with fermented treatment is preferred because it has a more attractive color, taste, and aroma compared to nonfermented cocoa butter.